Penicillium marneffei infection in an AIDS patient: A first case report from Malaysia - Ismail, Rokiah (1995)
We report a 39-year-old male who presented with tuberculous meningitis and was found also co be HIV-infected. In the course of his illness, he developed multiple opportunistic infections such as herpes genitalis, oesophageal candidiasis CMV retinitis and finally succumbed to Penicilium marneffei septicaemia.